ANALISIS YURIDIS TAFSIR KONSTITUSIONALITAS TERHADAP FRASE ORGANISASI ADVOKAT DALAM UNDANG-UNDANG NOMOR 18 TAHUN 2003 - Sofyan Joesoef; Idham Chalid; Jalaludin (Universitas Tadulako, 2024)
The purpose of this research is to find out the Constitutional Court's decision on the constitutionality interpretation of the phrase